INFRASTRUCTURE, RESOURCES, SERVICES EVALUATION AND GAP ANALYSIS OF INTEGRATED MATERNAL AND CHILD DEVELOPMENT SERVICES IN INDIA - Kaur, S.; Gupta, R.; Khan, I. D.; Jindal, S.; Prajapati, S.; Makkar, A.; Rajmohan, K. S. (International Journal of Medicine and Medical Research, 2019)
Background. Integrated Child Development Services (ICDS) is an Indian community-centric government program organized under Anganwadi centres catering to supplementary nutrition, health and preschool education, primary healthcare, growth monitoring and counselling the children under six years old along with their mothers. It is the world’s largest outreach program in a developing country covering a population of 1.35 billion; the variations in service delivery were analysed involving cross-sectional rural and urban Anganwadi centers in New Delhi. Methods. Data were collected by assessment of children and mothers, interview of Anganwadi workers and observation of service delivery parameters and conduction of activities. Infrastructural, beneficiaries, services and content were evaluated by a suitable pre-tested questionnaire based on the National Institute of Public Cooperation and Child Development (NIPCCD) evaluation proforma. The data was analysed by a descriptive statistics. Results. Gaps were found in respect of infrastructure, resources, health and nutrition facilities especially at rural Anganwadi centre which was inadequate in terms of implementation of nutrition and health program, supplementary nutrition, preschool education and nutrition rehabilitation centre for existing beneficiaries. Both Anganwadi centres were not catering for new WHO growth standards and adolescent health. Conclusions. Gaps found in respect of infrastructure, resources, health and nutrition facilities can affect performance of ICDS program and the services delivered by Anganwadi centres, which need a boost. Both urban and rural centres have a direct opportunity towards delivering adolescent health program focusing on nutrition and education of girls prior to their pregnancy, and adoption of new WHO growth standards.